Cover Picture: Anionic Bipyridyl Ligands for Applications in Metallasupramolecular Chemistry (Chem. Eur. J. 19/2014). Issue 19 (5th May 2014) - Pascu, Mirela; Marmier, Mathieu; Schouwey, Clément; Scopelliti, Rosario; Holstein, Julian J.; Bricogne, Gérard; Severin, Kay
<x xml:space="preserve">Abstract</x> Anionic bipyridyl ligands have interesting characteristics for applications in supramolecular coordination chemistry: 1) they are robust, rigid, and relatively long; 2) the lateral size and the solubility of the ligands can be modified by variation of the phenolatodioximato ligand; 3) the Zn‐based clathrochelates are luminescent; and 4) it is possible to incorporate diamagnetic or paramagnetic metal ions. For more details see the Full Paper by K. Severin et al. on page 5592 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>